Pemberdayaan Ekonomi Pesantren melalui Unit Usaha Berbasis Syari’ah di Pondok Pesantren Nurul Haramain, Narmada Kabupaten Lombok Barat - Syaiful Rahman; Riduan Mas’ud; Muh. Azkar (LP2M STIT Palapa Nusantara, 2023)
The economic empowerment of Islamic boarding schools is a form of dawah bil hal as well as a form of concrete implementation of their knowledge and can be an alternative and solution to the problems of balanced and resilient economic development in a sustainable manner. The purpose of this study was to determine the management of the Islamic boarding school's economy, the obstacles encountered and the solutions implemented in empowering the Islamic boarding school's economy through sharia-based business units at the Nurul Haramain Islamic Boarding School, Narmada, West Lombok Regency. This research method uses qualitative research with data collection techniques using interviews, observation and documentation. Data analysis was carried out in three stages, namely data reduction, data display and conclusion drawing. The results of this study indicate that the management of the pesantren economy through sharia-based business units at the Nurul Haramain Islamic Boarding School, Narmada, West Lombok Regency is carried out by carrying out planning which includes: determining the priority of the Islamic boarding school business work program, formulating goals to be achieved and adjusting the Islamic boarding school work program . Then organizing, actuating and controlling. Islamic boarding school economic management through these sharia-based business units such as mini banks and NH-Marts. Constraints faced include that some products are not yet known to the general public, there is still a lack of capital and a lack of human resources both in terms of knowledge and skills. Solutions made to overcome the obstacles faced are carried out by holding exhibitions, increasing human resources such as entrepreneurship training, bookkeeping, managerial, leadership and carrying out technical guidance and applying the 5C + 1S system, namely character, capacity, capital, collateral, condition and sharia.